1994
DOI: 10.1111/j.1476-5381.1994.tb14791.x
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin‐1β enhances capsaicin‐induced neurogenic vasodilatation in the rat skin

Abstract: This study examined the effect of interleukin‐1β (IL‐1β) on the capsaicin‐induced increase in cutaneous blood flow of anaesthetized rats as measured by laser Doppler flowmetry. The substances were administered by intraplantar subcutaneous injection of 10 μl‐volumes, saline being injected into one hindpaw and IL‐1β into the other. IL‐1β (0.5–500 pg) was without effect on blood flow on its own but dose‐dependently enhanced the hyperaemic response to intraplantar capsaicin (0.3 μg) up to 180% (P < 0.05) of the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0
4

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 32 publications
3
30
0
4
Order By: Relevance
“…(Ferreira et al, 1988;Poole et al, 1992). A first hint to a sensitization of thin afferent nerve fibers came from an enhancement of capsaicin-induced vasodilatation in rat skin in vitro because capsaicin as well as noxious heat activate the same ion channel in nociceptive neurons (Herbert and Holzer, 1994;Herbert et al, 1995;Tominaga et al, 1998). The ion channel is modulated by phosphorylation, and the IL-1RI pathway has been suggested to activate several serin kinases, e.g., IRAK (Cao et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…(Ferreira et al, 1988;Poole et al, 1992). A first hint to a sensitization of thin afferent nerve fibers came from an enhancement of capsaicin-induced vasodilatation in rat skin in vitro because capsaicin as well as noxious heat activate the same ion channel in nociceptive neurons (Herbert and Holzer, 1994;Herbert et al, 1995;Tominaga et al, 1998). The ion channel is modulated by phosphorylation, and the IL-1RI pathway has been suggested to activate several serin kinases, e.g., IRAK (Cao et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Because all neurons continuously fire at low basal rates, it is possible that low steady-state levels of CGRP are present due to basal release and turnover. In other tissues, CGRP release from sensory nerve endings can be stimulated by nociceptive stimuli and by inflammatory mediators such as IL-1 [6,7]. Thus, it is possible that CGRP secretion from nerve terminals in bone marrow could be enhanced by cytokines and soluble factors produced in the local bone marrow microenvironment as well as by factors produced at a distal site of inflammation or immune activation.…”
Section: Discussionmentioning
confidence: 99%
“…CGRP is released at these sites, along with substance P (SP), in response to nociceptive stimuli. Its release from local nerve endings is promoted by inflammatory mediators including pro-inflammatory cytokines and prostaglandins [6,7]. In addition to being a potent vasodilator, CGRP can directly influence lymphocyte and macrophage functions.…”
Section: Introductionmentioning
confidence: 99%
“…), their trachea was cannulated, blood pressure monitared continuously via a catheter in the right carotid artery, and rectal temperature maintained at 37.5-:38°C with a heating pad (Herbert and Holzer, 1994). Blood flow in the plantar skin of each hindpaw was recorded with a calibrated Iaser Doppler flowmeter (Periflux PF3, Perimed, Sweden) as described previously (Herbert and Holzer, 1994), blood flow being expressed in dimensionless perfusion units (PU).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously shown that the inflammatory cytokine interleukin-lß enhances the hyperaemia evoked by injection of capsaicin into the rat plantar hindpaw skin in a prostaglandin-dependent manner (Herbert and Holzer, 1994). Since the vasodilator effect of calcitonin gene-related peptide (CGRP), the major neuragenie mediator of the capsaicin-induced vasodilatation (Hughes and Brain, 1991;Brain et al, 1993), was not altered by interleukin-1ß it was concluded that the effect of the cytokine was brought about by sensitization of afferent neiVe endings to capsaicin (Herbert and Holzer, 1994).This inference was further tested here by examining the effect of interleukin-1/3 in rats in which thin afferent neurones bad been defunctionalized by systemic …”
mentioning
confidence: 99%